Guideline on safer conception in fertile HIV-infected individuals and couples - L-G Bekker; V Black; L Myer; H Rees; D Cooper; S Mall; C Mnyami; F Conradie; I Mahabeer; L Gilbert; S Schwartz (AOSIS, 2011)
Ninety years ago the isolation of insulin transformed the lives of people with type 1 diabetes. Now, models based on empirical data estimate that a 25-year-old person with HIV, when appropriately treated with antiretroviral therapy, can expect to enjoy a median survival of 35 years, remarkably similar to that for someone of the same age with type 1 diabetes. It is high time we normalised the lives of people living positively with HIV. This includes the basic human right to conceive and raise children. HIV-positive individuals may be in serodiscordant relationships or in seroconcordant relationships. As health care providers, it is our responsibility to ensure we understand the opportunities and risks of natural conception in these scenarios, so that we can help our patients to make informed decisions about their own lives. Most of all, it is our duty to make family planning in the setting of positive prevention as safe as we can. This includes informed decisions on contraception, adoption, fostering, conception and prevention of mother-to-child transmission. Some months ago a dedicated group of individuals, invited and sponsored by the Southern African HIV Clinicians Society, came together in Cape Town to devise guidance in this area, recognising that there are ideal strategies that may be outside the realm of the resource constraints of the public sector or health programmes in southern Africa. This guideline therefore attempts to provide a range of strategies for various resource settings. It is up to us, the providers, to familiarise ourselves with the merits/benefits and risks of each, and to then engage patients in meaningful discussions. All the above, however, is based on the premise and prerequisite that the subject of family planning is actively raised and frequently discussed in our patient encounters. Please find a link to the update of this guideline: http://sajhivmed.org.za/index.php/hivmed/article/view/399